FACTORS AFFECTING THE INDEPENDENCE OF GOVERNMENT AUDITORS OF BPKP REPRESENTATIVE OF EAST KALIMANTAN PROVINCE - Irwansyah Irwansyah; Fibriyani NurKhairin; NurAini NurAini (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
This study aims to determine whether the factors consisting of audit experience, knowledge, job stress scale, and reward may affect the independence of government auditors. This study uses primary data obtained from questionnaire. The population in this study is as many as 103 government auditors working at the Finance and Development Supervisory Agency (BPKP) of East Kalimantan Province with a total sample of 33 government auditors. The analysis tool used is multiple linear regression formula, while the hypothesis test is conducted using model feasibility test (F statistic test) and partial significance test (t statistic test). The result of simultaneous hypothesis test indicates that audit experience, knowledge, job stress scale, and reward simultaneously have positive effect on the independence of the government auditors. The result of partial significance test indicates that: (1) audit experience has no effect on the independence of the government auditors, (2) knowledge has positive effect on the independence of the government auditors, (3) job stress scalehas no effect on the independence the government auditors, and (4) reward has no effect on the independence of the government auditorsofthe Finance and Development Supervisory Agency(BPKP) Representative ofEast Kalimantan Province.INTRODUCTION